Vitamin C, Thiamine, and Hydrocortisone in the Treatment of Sepsis: A Meta-Analysis and Trial Sequential Analysis of Randomized Controlled Trials. (March 2022) - Zayed, Yazan; Alzghoul, Bashar N.; Banifadel, Momen; Venigandla, Hima; Hyde, Ryan; Sutchu, Selina; Khasawneh, Majd; Borok, Zea; Urbine, Daniel; Jantz, Michael; Reddy, Raju
Background: There is a conflicting body of evidence regarding the benefit of vitamin C, thiamine, and hydrocortisone in combination as an adjunctive therapy for sepsis with or without septic shock. We aimed to assess the efficacy of this treatment among predefined populations. Methods: A literature review of major electronic databases was performed to include randomized controlled trials (RCTs) evaluating vitamin C, thiamine, and hydrocortisone in the treatment of patients with sepsis with or without septic shock in comparison to the control group. Results: Seven studies met our inclusion criteria, and 6 studies were included in the final analysis totaling 839 patients (mean age 64.2 ± 18; SOFA score 8.7 ± 3.3; 46.6% female). There was no significant difference between both groups in long term mortality (Risk Ratio (RR) 1.05; 95% CI 0.85-1.30; P = 0.64), ICU mortality (RR 1.03; 95% CI 0.73-1.44; P = 0.87), or incidence of acute kidney injury (RR 1.05; 95% CI 0.80-1.37; P = 0.75). Furthermore, there was no significant difference in hospital length of stay, ICU length of stay, and ICU free days on day 28 between the intervention and control groups. There was, however, a significant difference in the reduction of SOFA score on day 3 from baseline (MD −0.92; 95% CI −1.43 to −.41; P < 0.05). In a trial sequential analysis for mortality outcomes, our results are inconclusive for excluding lack of benefit of this therapy. Conclusion: Among patients with sepsis with or without septic shock, treatment with vitamin C, thiamine, and hydrocortisone was not associated with a significant reduction in mortality, incidence of AKI, hospital and ICU length of stay, or ICU free days on day 28. There was a significant reduction of SOFA score on day 3 post-randomization. Further studies with a larger number of patients are needed to provide further evidence on the efficacy or lack of efficacy of this treatment.